Comparison of outcomes after hospitalization for worsening heart failure, myocardial infarction, and stroke in patients with heart failure and reduced and preserved ejection fraction. (30th December 2014) - Kristensen, Søren L.; Jhund, Pardeep S.; Køber, Lars; Preiss, David; Kjekshus, John; McKelvie, Robert S.; Zile, Michael R.; Anand, Inder S.; Wikstrand, John; Wedel, Hans; Komajda, Michel; Carson, Peter E.; et al.
Abstract Aims To investigate the prognostic significance of hospitalization for worsening heart failure (WHF), myocardial infarction (MI), and stroke in patients with chronic heart failure (HF). Methods and results We studied 5011 patients with HF and reduced EF (HF‐REF) in the CORONA trial and 4128 patients with HF and preserved EF (HF‐PEF) in the I‐Preserve trial. Adjusted hazard ratios (HRs) for death were estimated for 0–30 days and ≥31 days after first post‐randomization WHF, MI, or stroke used as a time‐dependent variable, compared with patients with none of these events. In CORONA, 1616 patients (32%) had post‐randomization first events (1223 WHF, 216 MI, 177 stroke), and the adjusted HR for mortality ≤30 days after an event was: WHF 7.21 [95% confidence interval (CI) 2.05–25.40], MI 23.08 (95% CI 6.44–82.71), and stroke 32.15 (95% CI 8.93–115.83). The HR for mortality at >30 days was: WHF 3.62 (95% CI 3.11–4.21), MI 4.41 (95% CI 3.23–6.02), and stroke 3.19 (95% CI 2.21–4.61). In I‐Preserve, 896 patients (22%) experienced a post‐randomization event (638 WHF, 111 MI, 147 stroke). The HR for mortality ≤30 days was WHF 31.77 (95% CI 7.60–132.81), MI 154.77 (95% CI 34.21–700.17), and stroke 223.30 (95% CI 51.42–969.78); for >30 days it was WHF 3.36 (95% CI 2.79–4.05), MI 3.29 (95% CI 2.14–5.06), and stroke 5.13 (95% CI 3.61–7.29). Conclusions In patients with both HF‐REF and HF‐PEF, hospitalization for WHF was associated with high early and late mortality. The early relative risk of death was not as great as following MI or stroke, but the longer term relative risk of death was similar following all three types of event. Numerically, more deaths occurred following WHF because it was a much more common event.